2017
DOI: 10.5812/jjhr.62415
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Male Condom Usage: With a Brief Discussion on Possible Effects of New Population Policies in Iran on Condom Usage

Abstract: Background: In spite of the fact that Iran is one of the most successful countries in family planning program yet the rate of condom usage among those, who are sexually active is low. As a result, recognizing barriers to condom usage can improve planning for condom promotion. Objectives: The main goal of this study was to examine the rate of condom usage and to determine factors influencing condom usage among couples in Shiraz city of Iran. This study also investigates the possible effects of new population po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 7 publications
0
8
0
Order By: Relevance
“…These policies are, however, controversial from both the ethical and health perspectives: they severely limit the reproductive rights and freedoms of Iranian women and couples and potentially exert negative impacts on reproductive health for both the mother and the child. 26 , 62 …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…These policies are, however, controversial from both the ethical and health perspectives: they severely limit the reproductive rights and freedoms of Iranian women and couples and potentially exert negative impacts on reproductive health for both the mother and the child. 26 , 62 …”
Section: Resultsmentioning
confidence: 99%
“…The restriction of fetal screening, the limiting of access to contraceptives and the tightening of the already strict rules on abortion are likely to lead to an increase in the number of newborns with physical and mental disabilities. 62–64 Concerns have also been voiced about the threat of severe punishment under the criminal code for performing illegal abortions. 13 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The impact of education in this research domain cannot be understated, as previous studies have underscored its pivotal role in mitigating the prevalence of unintended pregnancies. 45 , 46 For instance, Oulman et al 45 discovered that women with a high school education or lower had 1.71 times higher odds of unintended pregnancy compared to those with higher educational levels. Our study observed a positive association between women’s higher educational attainment and their awareness of the possibility of becoming pregnant shortly after childbirth before the resumption of the menstrual period.…”
Section: Discussionmentioning
confidence: 99%
“…It has also been shown that from 2015 to 2019, there were 121 million unintended pregnancies annually, resulting in 64 unintended pregnancies per 1,000 women aged 15–49 [ 3 ]. The prevalence of unintended pregnancies in Iran has been reported differently in various studies, ranging from 17% in the city of Shiraz to 27.8% in the city of Arak [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%